Evaluation of a warfarin bait for controlling invasive wild pigs (Sus scrofa). Issue 7 (13th March 2021) - Beasley, James C; Clontz, Lindsay M; Rakowski, Allison; Snow, Nathan P; VerCauteren, Kurt C
Abstract: BACKGROUND: Wild pigs ( Sus scrofa ) cause widespread environmental and economic damage, and as a result are subjected to extensive control. Current management strategies have proven insufficient, and there is growing interest in use of toxicants to control invasive populations of this species. In 2017 a low‐dose warfarin bait was federally approved for use in controlling wild pigs in the United States. However, no states have allowed use of this bait due to unanswered questions regarding welfare concerns, field efficacy, and non‐target impacts. RESULTS: All captive wild pigs fed 0.005% warfarin baits in no choice feeding trials succumbed in an average of 8 days from exposure. Behavioral symptoms of warfarin exposure included vomiting, external bleeding, abnormal breathing, incoordination, and limping. Postmortem examinations revealed hemorrhaging in organs and muscles, particularly the legs, gastrointestinal tract, and abdomen. Warfarin residues in tissues averaged 1.0 mg kg ‐1 for muscle, 3.9 mg kg ‐1 for liver, and 2.8 mg kg ‐1 for small intestines. Field testing revealed wild pigs required extensive training to access bait within pig‐specific bait stations, and once acclimated, exhibited reluctance to consume toxic baits, resulting in no mortalities across two separate field deployments of toxic bait. CONCLUSION: Our results suggest wild pigs are susceptible to low‐dose warfarin, and warfarin residues in pig tissues postmortem are generally low. However, although warfarin‐based baits are currently approved for use by the US Environmental Protection Agency, further improvements to pig‐specific bait delivery systems and bait palatability are needed, as well as additional research to quantify efficacy, cost, and non‐target impacts prior to widespread implementation. © 2021 Society of Chemical Industry. This article has been contributed to by US Government employees and their work is in the public domain in the USA. Abstract : Here we show wild pigs are susceptible to low‐dose warfarin baits, but when deployed in a field setting no wild pigs consumed a lethal dose, indicating improvements in palatability and delivery systems are needed prior to implementation. © 2021 Society of Chemical Industry. This article has been contributed to by US Government employees and their work is in the public domain in the USA.